Symptomatic pelvic hematoma following hysterectomy: risk factors, bacterial pathogens and clinical outcome - Henry H. Chill; Itshak Amsalem; Gilad Karavani; Sharon Amit; Abraham Benshushan; David Shveiky (BMC, 2020)
Abstract Background Pelvic hematoma is a common finding following hysterectomy which at times may become infected causing substantial morbidity. The aim of this study was to describe the incidence, clinical manifestation and identify risk factors for infected pelvic hematoma. We also attempted to identify specific bacterial pathogens which may cause this phenomenon. Methods We conducted a retrospective cohort study at a tertiary university teaching hospital. Included were all women who underwent hysterectomy and were diagnosed with a pelvic hematoma following surgery from 2013 to 2018. In an attempt to assess possible risk factors for infected pelvic hematoma women with asymptomatic pelvic hematoma were compared to women with an infected pelvic hematoma. Results During the study period 648 women underwent hysterectomy at our medical center. Pelvic hematoma was diagnosed by imaging in 50 women (7.7%) including 41 women who underwent vaginal hysterectomy and 9 women who underwent abdominal hysterectomy. In 14 (2.2%) cases the hematoma became infected resulting in need for readmission and further treatment. Women who underwent vaginal surgery were more likely to return with infected pelvic hematoma compared to women who underwent open abdominal or laparoscopic surgery (4.5% vs. 1.1%, p < 0.05). In 8 women bacterial growth from hematoma culture was noted. Enterococcus faecalis, was the most abundant pathogen to be isolated in this sub-group. Conclusion Vaginal route of hysterectomy is a risk factor for infected pelvic hematoma following hysterectomy. Most of these infections were caused by anaerobic bacteria which may not be sufficiently covered by current antibiotic prophylactic regimens.